Standing on the brink of change? The ME receptarium in Wellcome Library MS 409 - Moreno-Olalla, David (My University, 2014)
The following paper is intended to present the main features, mostly grammatical but not only, of a receptarium, that is a collection of medical recipes, contained in London, Wellcome Library, MS 409, ff. 16r–54v, 88r–98r and 99r–108v.
Keywords: Inglés medieval; Middle English; Wellcome Library MS 409; Receptarium